Ketidakaktifan yang Disengaja? Memahami Sikap Tiongkok dalam Negosiasi Isu Denuklirisasi Korea Utara - Mochammad A. R. Syarafi; Pasek A. Diwangkara; Brian Ainurrohman (Universitas Airlangga, 2019)
The bilateral meeting between the United States and North Korea, whichwas held in Hanoi in February 2019, has not resulted in any agreementbetween the two parties. Furthermore, North Korea’s construction activityof a nuclear development facility in Tongchan-ri has threatened the possibilityof any agreement between both states and has shown North Korea’spoor commitment to denuclearization. In order to understand the attitudeshown by North Korea, it is important to consider the presence of anotherdominant actor in East Asia, the People’s Republic of China (PRC). Thisresearch aims to study the significance of the North Korean denuclearizationissue for the PRC, as well as the PRC’s position in the issue. This researchutilizes a document-based data-collecting method, which includesofficial documents released by the PRC as well as literatures that havecarried out earlier studies on the topic. This research has shown that thePRC possesses significant interests and power in the denuclearization ofNorth Korea, which require the country to maintain an unclear stance inthe denuclearization process of North Korea.